The Role of Place Attachment in Promoting Refugees’ Well-Being and Resettlement: A Literature Review - Thomas Albers (MDPI AG, 2021)
Refugees are at great risk of developing mental health problems. Yet, little is known about how to optimally help this vulnerable group as there is a lack of evaluated refugee mental health interventions. The current article presents the results of a literature review which investigates the importance of place attachment for the promotion of refugees’ well-being in the resettlement process. This review concentrated on the most recent and current literature regarding the potential role, importance, and relevance of people–place bonds in the dynamic process of refugee resettlement. It examines literature from the field of positive and environmental psychology, highlighting key theoretical concepts and research findings as well as gaps in research. The review revealed that little is known about the dynamics of place bonding, while the debate rages on about the geometry of the psychological constructs of person–place relationships. Yet, knowing more about which needs should be satisfied for easing place bonding could be of crucial importance for facilitating refugee well-being. Ultimately, improving the knowledge and understanding of the phases of this dynamic process could be useful for a more successful implementation of refugee resettlement practices and activities.